A molecular phylogeny of rose chafers (Coleoptera: Scarabaeidae: Cetoniinae) reveals a complex and concerted morphological evolution related to their flight mode - Šípek, Petr; Fabrizi, Silvia; Eberle, Jonas; Ahrens, Dirk (Molecular phylogenetics and evolution, 2016)
Rose chafers (Cetoniinae) are a large group of flower visitors within the pleurostict Scarabaeidae that are characterized by their distinctive flight mode with nearly closed forewings. Despite their popularity, this is the first study to use molecular data to infer their phylogenetic relationships. We used partial gene sequences for 28S rRNA, cytochrome oxidase I (cox1) and 16S rRNA (rrnL) for 299 species, representing most recognized subfamilies of Scarabaeidae, including 125 species of Cetoniinae. Combined analyses using maximum parsimony, maximum likelihood and Bayesian inferences recovered Cetoniinae as monophyletic in all analyses, with the sister clade composed of Rutelinae and Dynastinae. Rutelinae was always recovered as paraphyletic with respect to Dynastinae. Trichiini sensu lato (s.l.) was recovered as a polyphyletic clade, while Cetoniini s.l. was recovered as paraphyletic. The inferred topologies were also supported by site bootstrapping of the ML trees. With the exception of Cremastochelini, most tribes of Cetoniinae were poly- or paraphyletic, indicating the critical need for a careful revision of rose chafer classification. Analysis of elytral base structure (including 11 scored characters) in the context of phylogeny, revealed a complex, concerted and rapid transformation of the single trait elements linked to a modified flight mode with closed elytra. This appears to be unlinked to the lateral sinuation of the elytra, which originated independently several times at later stages in the evolution of the group.
Keywords: Animals; RNA ribozomální 28S; biologická evoluce; Electron Transport Complex IV; RNA, Ribosomal, 28S; Coleoptera; Cetoniinae; Wings, Animal; RNA, Ribosomal, 16S; brouci; Bayesova věta; DNA; respirační komplex IV; Bayes Theorem; Elytral base; Phylogeny; Systematics; Sequence Analysis, DNA; křídla zvířecí; Scarabaeidae; zvířata; sekvenční analýza DNA; Biological Evolution; fylogeneze; Flight mode; RNA ribozomální 16S